Effect of Increasing Levels of Dietary Hemp Seed Cake on Egg Quality in Commercial Laying Hens - Kasula, Rajasekhar; Solis , Fausto; Shaffer, Byron; Connett, Frank; Barrett, Chris; Cocker, Rodney; Willinghan, Eric (International Journal of Poultry Science, 2021)
Background and Objective: Hemp seed and hemp seed products such as Hemp Seed Cake (HSC) have shown to increase unsaturated fatty acid (FA) profile in eggs, including linoleic acid, known to increase egg weight and α-linolenic fatty acids. However, the use of hemp products in animal feed is still a concern due to the potential residues of the of Δ-9 tetrahydrocannabinol, a psychoactive substance present in the hemp plant. No significant published research is available on the effect of dietary HSC on egg quality parameters in commercial laying hens. The objectives of this study was to determine the effect of dietary HSC on egg quality, external (egg weight, egg mass, eggshell strength, eggshell thickness) and internal (Haugh units, egg yolk pigmentation, egg lutein, egg fatty acids, egg heavy metals and egg cannabinoid residues). Materials and Methods: Eight hundred (800) Bovan caged hens in lay at 30 weeks of age were distributed into 4 treatments of 200 hens per treatment based on inclusion levels (0, 10, 20 and 30%) of hemp seed cake (HSC). Each treatment comprised of 8 cages of 25 hens each that served as replicates. The observations per protocol were made over a period of 16 weeks following a 3-week acclimation. Results: HSC feeding to commercial laying hens did not adversely affect egg weigh, egg mass; however, positive effects of HSC supplementation was observed on eggshell strength and the polyunsaturated fatty acids including linoleic and linolenic fatty acids. HSC also improved egg lutein, yolk pigmentation and Haugh units. The cannabinoids residues in eggs was below the detectable level. Conclusion: The results of this study confirm that HSC fed to laying hens enhanced the overall value of the eggs with increased deposition of beneficial unsaturated fatty acids, yolk pigmentation, Haugh units and lutein content and the trial also demonstrated that feeding HSC to laying hens did not contribute to tetrahydrocannabinol (THC) or cannabinoid residues in eggs.